2005
DOI: 10.1074/jbc.m408194200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Human RSK4, a New 90-kDa Ribosomal S6 Kinase, Reveals Constitutive Activation in Most Cell Types

Abstract: The 90-kDa ribosomal S6 kinases (RSK1-3) are important mediators of growth factor stimulation of cellular proliferation, survival, and differentiation and are activated via coordinated phosphorylation by ERK and 3-phosphoinositide-dependent protein kinase-1 (PDK1). Here we performed the functional characterization of a predicted new human RSK homologue, RSK4. We showed that RSK4 is a predominantly cytosolic protein with very low expression and several characteristics of the RSK family kinases, including the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 55 publications
(29 reference statements)
4
91
2
Order By: Relevance
“…A higher expression of these two putative tumor suppressor genes in breast cancer biopsy samples compared with adjacent normal mammary tissues conflicts with previous in vitro studies that suggest that these two genes have growth inhibitory activity (19)(20)(21)(22)(23). However, this is the first study to screen the mRNA and protein expression of these two genes (RbAp46 and Rsk4) and other putative tumor suppressor gene (Cldn2) in human breast cancer and adjacent normal tissues.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A higher expression of these two putative tumor suppressor genes in breast cancer biopsy samples compared with adjacent normal mammary tissues conflicts with previous in vitro studies that suggest that these two genes have growth inhibitory activity (19)(20)(21)(22)(23). However, this is the first study to screen the mRNA and protein expression of these two genes (RbAp46 and Rsk4) and other putative tumor suppressor gene (Cldn2) in human breast cancer and adjacent normal tissues.…”
Section: Discussioncontrasting
confidence: 51%
“…Surprisingly, we found that a large percentage of breast cancer cases had high expression of two putative tumor suppressor genes (Rsk4 and RbAp46), which have been shown to be growth inhibitory genes in in vitro studies (19)(20)(21)(22)(23). The RbAp46 gene showed increased expression in 79% of cases (15 of 19) compared with adjacent mammary tissues.…”
Section: Expression Of Tumor Suppressor Genes and Oncogenes Mrna In Hmentioning
confidence: 99%
“…Initially, RPS6KA1 (p90 Rsk-1) and RPS6KA3 (p90 Rsk-2) were identified (Frodin and Gammeltoft, 1999). Subsequently, RPS6KA2 (p90 Rsk-3) was isolated and more recently, RPS6KA6 (p90 Rsk-4) (Moller et al, 1994;Zhao et al, 1995;Yntema et al, 1999;Dummler et al, 2005). RPS6KA4 (Msk-1) and RPS6KA5 (Msk-2) are less homologous to the first four members of the RSK family.…”
Section: Discussionmentioning
confidence: 99%
“…pMT2 plasmids expressing RPS6KA1 (RSK1) and RPS6KA3 (RSK2) were obtained from Dr M Greenberg (Xing et al, 1998); RPS6KA2 (RSK3) and K91A-RPS6KA2 (K91A-RSK3) from Dr C Bjorbaek ; and RPS6KA6 (RSK4) was obtained from Dr M Fro¨din (Dummler et al, 2005). Full-length cDNA of RPS6KA genes were released from the pMT2 vector using EcoRI digestion and subcloned with or without a HA tag (as a linker with overhangs for restriction sites KpnI and BamHI, (CATG-TACCCATAC-GATGTTCCAGATTACGCTGGG) into the eukaryotic expression vectors, pcDNA3/neo, pcDNA3.1, pcDNA4/TO and pcDNA5/TO (Invitrogen, Paisley, Strathclyde, UK), and pEGFP-C3 (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Work using PDK1 −/− embryonic stem cells confirmed that PDK1 was required for the activation of RSK1, RSK2 and RSK3 [20]. Surprisingly, however, the use of these knockout cells has also demonstrated that the activation of MSK1 [20] and RSK4 [21] is independent of PDK1, and that T-loop phosphorylation for these kinases occurs via a different mechanism.…”
Section: Introductionmentioning
confidence: 99%